Factorial design of experiments for extraction and screening analysis of organic compounds in hydrochar and its process water of sugar cane bagasse and vinasse - Laranja, Márcio Justi [UNESP]; da Silva, Renata Cristina Júlio [UNESP]; Bisinoti, Márcia Cristina [UNESP]; Moreira, Altair Benedito [UNESP]; Boscolo, Maurício [UNESP]; Ferreira, Odair Pastor; de Almeida Melo, Camila [UNESP] (Springer Nature, 2020)
The extraction of non-volatile (NVOC), semi-volatile (SVOC), and volatile (VOC) organic compounds in water and soil samples follows well-defined protocols, already described in the specialized literature. However, for environmental matrices that are either new, complex, or difficult to define, an adaptation of the extraction procedures needs to be made. Thus, the main purpose of this paper was to find the best conditions for the extraction of NVOC, SVOC, and VOC in complex matrix samples (hydrochar-HC and process water-PW) resulting from the hydrothermal carbonization of sugar cane bagasse and vinasse. For this, a factorial design (FD) was carried out for each type of extraction and sample. Solvent and temperature were the most determining parameters for the extraction processes. The best extraction conditions for NVOC from HC were obtained using acetone, during 8 h of reflux at Soxhlet and 1.00 g of HC (50 NVOCs), while for SVOC the best conditions were those using acetone, 40 min of ultrasound, and 1.00 g of HC (50 SVOCs). For NVOC from PW, the derivatization conditions that allowed the best extraction were found at 80 °C, 30 min, and 150 μL of PW (36 NVOCs), while for SVOC, the best conditions of extraction were those using dichloromethane and 20 min in single extraction (34 SVOCs). For VOC from HC, the best conditions were 80 °C and 30 min (39 VOCs), while, from PW, these were 40 °C and 30 min (48 VOCs) of headspace equilibrium. In this way, FD enabled the adaptation of the extraction procedures for hydrochar and process water, making screening by gas chromatography-mass spectrometry (GC-MS) analysis possible.
Keywords: Complex matrix; Factorial design; Hydrothermal carbonization; Organic compounds; Sugar cane bagasse; Vinasse